The Effect of Information Sharing, Knowledge Sharing, and Social Capital on Business Performance Mediated by Innovation (Study on Small Food Industry in Pekanbaru City - Rani Sagita Hilmawati; Samsir Samsir; Iwan Nauli Daulay; Prima Andreas Siregar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
The increase in the number of SMEs every year in the city of Pekanbaru creates high, dynamic, and turbulence competition that demands business actors to continue to improve supply chain management, knowledge sharing, social capital and innovation so that their business performance increases to provide added value and excel in competition. This study aims to determine the effect of Information Sharing, Knowledge Sharing and Social Capital on Business Performance mediated by innovation. This study uses data analysis tools and structural equation modelling (SEM) using Smart-PLS program ver 3.0. The sampling technique chosen is the Cluster Sampling method (236 small food industry players in Pekanbaru City). The study results show that: Information Sharing has a positive and not significant effect on innovation. Knowledge sharing and social capital have a positive and significant impact on innovation. Information sharing and social capital positively and significantly affect business performance. Knowledge sharing has a positive and not significant effect on the performance of the business. Innovation has a positive and significant effect on business performance. Information sharing and social capital through innovation on performance business have a positive but insignificant effect. Knowledge sharing through innovation on business performance has a positive and significant effect.